Efektivitas Adsorben Karbon Dioksida Berdasarkan Kapasitas Adsorpsi, Waktu Tembus, dan Keamanan: Tinjauan Naratif - Phalosa, Ghani; Riadi, Taufik; Syahputra, M. Keflin (Journal of Research and Education Chemistry, 2026)
Carbon dioxide accumulation in enclosed environments is a critical challenge due to its direct impact on health, cognitive performance, and operational safety. Although various carbon dioxide sorbents have been developed, existing studies generally address sorption capacity, saturation time, or safety aspects separately, resulting in fragmented evidence and not yet providing comprehensive guidance for integrated performance assessment. This study aims to address this gap through a comparative and multidimensional evaluation of various carbon dioxide sorbents based on sorption capacity, saturation time, and safety aspects. The method used is a narrative literature review with systematic collection and comparative synthesis of reputable scientific publications discussing chemical reaction-based sorbents, such as soda lime, lithium hydroxide, and calcium hydroxide, as well as physical adsorption-based adsorbents, such as activated carbon, zeolites, and metal-organic frameworks. The analysis results indicate that chemical reaction-based sorbents generally have higher sorption capacity due to the rapid chemical reaction, but potentially experience shorter saturation times and operational risks related to exothermic reactions and the formation of byproducts. In contrast, physical adsorption-based adsorbents tend to exhibit more stable dynamic performance and better regeneration ability, despite their relatively moderate sorption capacity. It is concluded that sorption capacity alone is insufficient to predict operational effectiveness. This review offers a performance-tradeoff-based evaluation framework as a basis for selecting safer and more reliable carbon dioxide sorbents in enclosed environments.